2001
DOI: 10.1128/aac.45.12.3517-3523.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of Mutations Contributing to Fluoroquinolone Resistance in Clinical Isolates of Streptococcus pneumoniae

Abstract: Twenty-one clinical isolates of Streptococcus pneumoniae showing reduced susceptibility or resistance to fluoroquinolones were characterized by serotype, antimicrobial susceptibility, and genetic analyses of the quinolone resistance-determining regions (QRDRs) of gyrA, gyrB, parC, and parE. Five strains were resistant to three or more classes of antimicrobial agents. In susceptibility profiles for gatifloxacin, gemifloxacin, levofloxacin, moxifloxacin, ofloxacin, sparfloxacin, and trovafloxacin, 14 isolates ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 52 publications
(62 reference statements)
3
56
2
2
Order By: Relevance
“…A novel Q90H change was found in ParC of one isolate, and a novel S80P change was found in another; both changes appeared to play a role in fluoroquinolone resistance. Some isolates (15 of 81; 18.5%) possessed three QRDR A minority of GyrB changes were implicated in resistance, as has been found previously (5,21,38). Surprisingly, 13 instances of ParE alterations (D435N and E474K in the main and one novel A325V change) occurred, which is greater than the number found in previous studies (3,5,21,38).…”
Section: Resultscontrasting
confidence: 53%
“…A novel Q90H change was found in ParC of one isolate, and a novel S80P change was found in another; both changes appeared to play a role in fluoroquinolone resistance. Some isolates (15 of 81; 18.5%) possessed three QRDR A minority of GyrB changes were implicated in resistance, as has been found previously (5,21,38). Surprisingly, 13 instances of ParE alterations (D435N and E474K in the main and one novel A325V change) occurred, which is greater than the number found in previous studies (3,5,21,38).…”
Section: Resultscontrasting
confidence: 53%
“…These percentages are reflective of the average susceptibility rates for penicillin and erythromycin in the United States and Canada (9,10,23). Weigel et al reported a similar finding (41). In contrast, Corso et al found that 65% of 20 fluoroquinoloneresistant isolates had reduced susceptibility to penicillin (6).…”
Section: Discussionmentioning
confidence: 56%
“…For this study, naturally occurring fluoroquinolone resistance mutations were placed in the serotype 19F strain EF3030 by using established techniques (17). Briefly, 1,325-bp fragments of gyrA and 778 bp of parC were amplified by polymerase chain reaction from 2 previously characterized (18) clinical isolates of QRSP (CT01147 and UAB169; gemifloxacin MIC = 1 µg/mL) by using the primers shown in the Table. Phenotypic expression was carried out for 2 to 24 h. First-step trans-formants were generated by the introduction of a parC or gyrA fragment, and these were selected on 0.06 µg/mL gemifloxacin (SmithKline Beecham Pharmaceuticals, Collegeville, PA, USA).…”
Section: Generation Of Fluoroquinolone-resistant Mutantsmentioning
confidence: 99%